URGENSI STANDAR OPERATING PROCEDURE (SOP) DALAM PELAYANAN PUBLIK ( SUATU TINJAUAN LITERATUR - La Ode Muhammad Ichwan Sjachrawy; Djoni Tepu; Hauziah Basir. B; Neni Susanti; Maudhy Satyadharma; Shinta Surya Idrus (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
In bureaucratic practice, public services often involve many stages, work units, and officers, so that without standard procedures, the service process is prone to irregularities, inconsistencies, and even deviations. Standard Operating Procedures (SOPs) exist to answer the need for work standards that can be followed consistently by all service personnel. SOPs have an important role in creating structured, efficient, transparent, and accountable services. This study aims to examine the urgency of implementing Standard Operating Procedures (SOPs) in public services through a literature study approach. This research was conducted using a literature review method through a literature study approach and a narrative model. The results of the study based on literature analysis indicate that SOPs as a standardization of public services, SOPs play a role in increasing the effectiveness and efficiency of public services, SOPs encourage service transparency, and are able to increase public satisfaction with the services provided.